Probing Polyoxometalate–Protein Interactions Using Molecular Dynamics Simulations. Issue 43 (9th September 2016) - Solé‐Daura, Albert; Goovaerts, Vincent; Stroobants, Karen; Absillis, Gregory; Jiménez‐Lozano, Pablo; Poblet, Josep M.; Hirst, Jonathan D.; Parac‐Vogt, Tatjana N.; Carbó, Jorge J.
Abstract: Invited for the cover of this issue is the group of Jorge J. Carbó at the University Rovira i Virgili. The image depicts the influence of polyoxometalate properties on their interactions with biomolecules. Read the full text of the article at10.1002/chem.201602263 . Abstract : " In analogy with our gravitationally bound solar system, the protein corresponds to the central star and POMs are the planetary bodies ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 15280 ff. (DOI:10.1002/chem.201602263 ).